Preparation and Properties of Novel In-situ Composite Materials Based on Polyethylene-Polyamide Oriented Blends - Dencheva, Nadya Vasileva (2008)
The objective of this study is to manufacture and investigate novel nanostructured polymer composites (NPC) based on oriented blends of high-density polyethylene (HDPE) and polyamide 6 (PA6). Conventional polymer processing techniques are used for this purpose including extrusion blending, cold drawing and compression molding. Thus, various polymer blends are prepared comprising 10 and 20 wt% of PA6 and 0-10 wt% of a copolymeric compatibilizer. These blends are cold-drawn to high draw ratios and the oriented strands so produced are further compression molded at various temperatures between the melting points of HDPE and PA6. All NPC obtained are characterized by microscopy techniques, solid state NMR, mechanical tests and wide- and small-angle X-ray scattering from synchrotron. The mechanical and structural data of NPCs are discussed with relation with the polyamide fibrils’ orientation, as well as with the effect of compatibilizer at the matrix-fibrils interface.